ANALISIS RAB STRUKTUR BETON GEDUNG RSUD YOGYAKARTA MEGGUNAKAN REVIT - Sayifullah Bustomi Abiyasa; M. Afif Shulhan; Dimas Langga Chandra Galuh (RENOVASI : Rekayasa Dan Inovasi Teknik Sipil, 2024)
The analysis of the Bill of Quantities (BOQ) for the concrete structure of the RSUD Yogyakarta building is an analytical activity that uses Autodesk Revit Software. The issue that arises is estimating the costs and identifying which items are calculated using Revit. The solution to this problem using Autodesk Revit Software is by identifying the modeling and then extracting the volume of each work item, such as reinforcement and rebar, within Autodesk Revit. The calculation results using Autodesk Revit show the volume of each work item. For the foundation work, it requires 159.3 m³ for concrete pouring and 18,658.6 kg for rebar. For the first floor, concrete pouring requires 174.58 m³ and rebar weighs 29,307.6 kg. On the second floor, the concrete pouring volume is 182.06 m³ with rebar weighing 27,196.17 kg. The third floor requires 139.81 m³ of concrete and 21,810.75 kg of rebar. Finally, for the concrete roof deck, the rebar volume is 25.98 m³ with rebar weighing 1,572.99 kg. Thus, the total concrete pouring volume is 681.73 m³, and the rebar weight is 98,546.17 kg. From the volume, an estimation of the reinforcement and rebar costs for each work item is generated. The foundation work requires a cost of IDR 373,090,357.00 for concrete pouring and IDR 1,758,704,534.00 for rebar. For the first floor, the concrete pouring costs IDR 107,569,354.00, and the rebar costs IDR 962,141,433.00. On the second floor, the concrete pouring costs IDR 97,560,372.00, with rebar costing IDR 1,261,605,190.00. The third floor requires IDR 50,112,904.00 for concrete pouring and IDR 696,583,946.00 for rebar. Finally, for the concrete roof deck at a height of 12.45 m, the rebar costs IDR 49,215,359.00, with rebar totaling IDR 685,800,691.00. Thus, the total overall cost for the RSUD Yogyakarta building is IDR 9,065,085,905.00.